Factors related to apical periodontitis in a southern Brazilian population: a multilevel analysis - Monika Lamas FERREIRA; Mônica Pagliarini BULIGON; Camila Silveira SFREDDO; Gabriela Salatino LIEDKE; Renata Dornelles MORGENTAL (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The aim of this cross-sectional study was to evaluate the effects of individual-level and tooth-level factors on apical periodontitis (AP) in an urban population in southern Brazil. A random sample of digital panoramic radiographs (n = 545) from a dental school database was evaluated. The diagnosis of AP was determined by using a dichotomous scale (yes/no). AP was assessed according to gender, age, presence and quality of endodontic treatment (ET), presence of an intracanal post, coronal condition, and dental group. Data were analyzed descriptively and through multilevel Poisson regression analysis, considering teeth characteristics (level 1) nested in individuals (level 2). In this sample of 545 participants, the prevalence of AP was 49.5% (n =2 70) and ET was 43.5% (n = 237). Considering 13,595 teeth, AP was identified in 596 (4.4%) and ET in 617 (4.5%). Of the teeth with ET, 153 (24.8%) presented AP. Among individual-level factors, the disease was not significantly associated with gender or age. For tooth-level factors, AP was significantly associated with ET quality: teeth with short ﬁllings (< 3 mm) and teeth with over-fillings had 2.77 (CI: 1.95-3.94, p < 0.001) and 1.08 (CI: 0.39-2.98, p < 0.001) higher prevalence of AP, respectively. There was no association between AP and age, gender, dental group, coronal condition, or the presence of an intracanal post. AP was highly prevalent in this population, and multilevel analysis indicated a significant association with ET quality.